2008
DOI: 10.1111/j.1440-1843.2008.01276.x
|View full text |Cite
|
Sign up to set email alerts
|

Pleural fluid viscosity may help identifying malignant pleural effusions

Abstract: High pleural fluid viscosity may suggest a potential diagnosis of malignant pleural effusion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 16 publications
0
10
0
Order By: Relevance
“…IL‐8 provided the most benefit (sensitivity 84%, specificity 82%), but overall IL‐8 and CRP were not superior and provided similar diagnostic accuracy as had been reported for other classic parameters such as pleural fluid pH. An interesting study postulated that neoplastic cells may increase pleural fluid viscosity 22 and found that it was a significant determinant with an odds ratio of > 6 (95% CI: 1.32–29.8). Further investigations in other disease conditions associated with exudates are clearly merited.…”
Section: Pleural Diseasementioning
confidence: 84%
“…IL‐8 provided the most benefit (sensitivity 84%, specificity 82%), but overall IL‐8 and CRP were not superior and provided similar diagnostic accuracy as had been reported for other classic parameters such as pleural fluid pH. An interesting study postulated that neoplastic cells may increase pleural fluid viscosity 22 and found that it was a significant determinant with an odds ratio of > 6 (95% CI: 1.32–29.8). Further investigations in other disease conditions associated with exudates are clearly merited.…”
Section: Pleural Diseasementioning
confidence: 84%
“…Pleural fluid viscosity is influenced by its cellular constituents and macromolecule composition. 1 Hyaluronic acid is a ubiquitous high molecular weight linear glycosaminoglycan that is present in abundance in the extracellular matrix. 2 Hyaluronic acid has been detected in the pleural fluid of a variety of malignant and nonmalignant conditions that includes mesothelioma, for which it also has diagnostic and prognostic significance.…”
Section: Discussionmentioning
confidence: 99%
“…Pleural fluid viscosity is influenced by cellular constituents and macromolecule composition, with protein being the major component [3]. Highly viscous pleural effusions are generally due to an exudative process such as infection or malignancy [4].…”
Section: Discussionmentioning
confidence: 99%